POLA INTERAKSI GURU DAN SISWA DALAM PEMBELAJARAN ONLINE MATA PELAJARAN PAI KELAS VII DI SMPN 2 PERAK JOMBANG - Nisak, Khoirotun; Rohmah, Hidayatur (Universitas KH. A. Wahab Hasbullah, 2021)
The purpose of this study was to determine the pattern of interaction between teachers and students in PAI learning. To find out the interaction patterns of teachers and students in online learning PAI subjects. To determine the factors supporting and inhibiting the interaction of teachers and students in online learning PAI subjects. This type of research is descriptive qualitative, namely research proposed to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions and thoughts of people, both individually and in groups. This research was conducted in Class VII SMPN 2 Perak Jombang. This type of research is descriptive qualitative, namely research proposed to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions and thoughts of people, both individually and in groups. The results of this study are 1) The interaction patterns of teachers and students interact well with each other. Students are more enthusiastic than during online learning, students are more focused when they are face to face with the teacher and the ongoing lesson. 2) The pattern of interaction of teachers and students in online learning PAI subjects Where online learning must require innovations from educators so that students are not bored with the learning process